2022
DOI: 10.3390/biology11010073
|View full text |Cite
|
Sign up to set email alerts
|

The Neonicotinoid Thiacloprid Interferes with the Development, Brain Antioxidants, and Neurochemistry of Chicken Embryos and Alters the Hatchling Behavior: Modulatory Potential of Phytochemicals

Abstract: The present experiment was performed to investigate the toxic impact of thiacloprid (TH) on the brain of developing chicken embryos and also to measure its influence on the behavioral responses of hatchlings. The role of chicoric acid (CA) and rosmarinic acid (RA) in modulating the resulted effects was also investigated. The chicken eggs were in ovo inoculated with TH at different doses (0.1, 1, 10, and 100 ug/egg). TH increased the mortality and abnormality rates and altered the neurochemical parameters of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…These changes may suggest a nervous system functioning deficit. These altered functions caused by TMX may be due to the identified oxidative damage, and they are most likely linked to neuronal dysfunction, as previously suggested by Farag et al ( 2022 ). According to Saied and Hassan ( 2014 ), BPA (endocrine disruptor) such as TMX can disrupt dopaminergic transmission by altering various processes such as DA synthesis, release, and turnover, as well as the expression of both DA transporters and receptors.…”
Section: Discussionsupporting
confidence: 57%
“…These changes may suggest a nervous system functioning deficit. These altered functions caused by TMX may be due to the identified oxidative damage, and they are most likely linked to neuronal dysfunction, as previously suggested by Farag et al ( 2022 ). According to Saied and Hassan ( 2014 ), BPA (endocrine disruptor) such as TMX can disrupt dopaminergic transmission by altering various processes such as DA synthesis, release, and turnover, as well as the expression of both DA transporters and receptors.…”
Section: Discussionsupporting
confidence: 57%
“…In agreement with our data, CA ameliorated the oxidative damage and enhanced the antioxidant capacity in the liver of rats poisoned with methotrexate ( Hussein et al, 2020 ) and in HepG2 cells treated with H 2 O 2 and larval zebrafish model ( Ma et al, 2018 ). Moreover, CA ameliorated the oxidative stress induced by TH in the brain of hatchlings ( Farag et al, 2022b ) and lungs of LPS-treated mice ( Ding et al, 2019 ). The antioxidant activity of CA can be returned to its efficient free radical scavenging potential ( Zhu et al, 2018 ) and via the activation of the Keap1/Nrf2 and HO-1 transcriptional pathways responsible for the expression of antioxidant proteins ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our experimental studies demonstrated the in ovo neurotoxicity effects of TH during chick embryo development that affects brain development and hatching behavior ( Farag et al 2021 ; Alagawany and Farag 2022 ; Farag et al, 2022b ). Preimplantation embryos of rabbits and mice exposed to TH in-vitro showed increased apoptosis incidence and decreased cell proliferation in the blastocysts ( Babeľová et al, 2017 ; Arain et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exposure to thiacloprid may also be linked to the inflammatory processes occurring in the other organs. Thiacloprid neurotoxicity was also suggested to be due to its functioning as both an antagonist and agonist at the nAChR (145,146), which needs to be confirmed by future studies. Knowing that the different generations of neonicotinoids do not have the same properties (absorption, metabolism, interaction with receptors, etc.…”
Section: Mice and Physiological Barriersmentioning
confidence: 95%
“…In general, stimulation in the posterior hypothalamus (PH) and lateral hypothalamus (LH) increases the arterial pressure and heart rate (HR), whereas stimulation in the POA often has opposite effects(66). The PVN, the right anterior aspect of the LH/supraoptic nuclei (SON), and the AN have been proposed to have cardiovascular regulatory activity(145). There are six established hypothalamic-…”
mentioning
confidence: 99%